Peran Pencahayaan Buatan Spa dalam Komparasi Variabel Relaksasi dan Variabel Kondisi Pencahayaan Buatan pada Spa - Qalbi, Aninda Samrati; Wibisono, Andriyanto (Serat Rupa: Journal of Design, 2024)
Work fatigue can have a negative impact on psychological conditions and can have a stressful impact on life, with minimal duration of rest time, humans need adequate rest time physically and mentally. Spa is one of the shortcuts to regain physical and mental fitness. Spa is a body care activity through massage to improve blood circulation to get relaxation so as to relieve stres. In creating a comfortable space, many elements need to be considered. Like the five human senses. In essence, the five human senses work together and provide experience of space. The sense of sight is a very important sense in the experience of space. Therefore artificial lighting is an interior element that needs attention. Because artificial lighting has a very important role in a person's mood so that it can help the relaxation process. The purpose of this research is to prove that artificial lighting has a role in the relaxation process. The research object is at Sendja Reflexology & Wellness in the city of Bandung with a focus on the VIP room. Comparative qualitative research method, data collection was carried out by comparing the theoretical variables of artificial lighting in the relaxation process and the condition of the Sendja Reflexology & Wellness VIP treatment room. Research data was obtained by questionnaire to 30 customers of Sendja Reflexology & Wellness. 94% of respondents stated that artificial lighting has a role in the relaxation process at Sendja Reflexology & Wellness.